Marketing and Business Management Improvement through Utilization of Digital Technology at Pujon’s MSMEs Malang - Ja'far, Handoko; Ahmad Luqman Hakim; Muhammad Kholish Aziz; Muhammad Imaduddin Ramadhan; Muhammad Nizar Faqih; Rafli Nur Alamsyah (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Madiredo Village, Pujon District's micro, small, and medium-sized enterprises (MSMEs) are the target of this research-based community service project, which uses digital technology to enhance marketing and business management in the digital age. By incorporating digital tools such as social media, e-commerce systems, and financial management software into their operations, the program aims to help rural MSMEs address the challenges they face. Through mentorship and instruction, the project is meant to raise operational efficiency, business management openness, and market reach. The data shows that businesses have been able to broaden their clientele and simplify operations utilizing digital technology, therefore positively impacting them. Among the obstacles found were inadequate internet access, poor digital literacy, and a lack of technical training among company operators. The study stresses the necessity of working together, village governments, schools, and companies, to improve the digital capacity of the community to solve these difficulties. Madiredo Village can fully realize the promise of digital technology to promote sustainable local economic development and empower its MSMEs in the digital economy by encouraging such synergies.